2010
DOI: 10.1007/s12272-010-0408-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isolated compounds from Catalpa ovata on the T cell-mediated immune responses and proliferation of leukemic cells

Abstract: Three compounds were isolated from the ethyl acetate soluble fraction of the methanolic extract of the leaves of Catalpa ovata (Bignoniaceae) through repeated column chromatography. We investigated the effects of these compounds on T cell-mediated responses for tumor surveillance and proliferation in U937, HL60, and Molt-4 leukemia cells. Compounds 1-3 inhibited proliferation of those cells in a dose-dependent manner. Compound 3 showed mild effect in Molt-4 cell cytotoxicity. Compound 3 enhanced gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recent studies related to C. ovata have been mainly focused on the components with antitumor, anti-inflammatory, and fungal pathogen inhibition effects in the stem and bark [12,[14][15][16][17][18][19][20]. Besides, some relevant researches also put emphasis on the antioxidant, antitumor and anti-inflammatory of C. ovata leaves [9,19,21,22]. With respect to C. ovata seeds, some researchers have only reported that fatty acids in seed oil have an inhibitory effect on rodent colon cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies related to C. ovata have been mainly focused on the components with antitumor, anti-inflammatory, and fungal pathogen inhibition effects in the stem and bark [12,[14][15][16][17][18][19][20]. Besides, some relevant researches also put emphasis on the antioxidant, antitumor and anti-inflammatory of C. ovata leaves [9,19,21,22]. With respect to C. ovata seeds, some researchers have only reported that fatty acids in seed oil have an inhibitory effect on rodent colon cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Mey., C. fargesii Bur., variant of C. tibetica Forrest, C. speciosa Ward., and C. fargesii f. duclouxii Dode, respectively. Previous phytochemical investigations indicated that iridoids and naphthoquinones were the main constituents of Catalpa plants [ 3 – 8 ]; C. ovata G. Don have showed antifungal activity [ 9 , 10 ], anti-inflammatory activity [ 11 15 ], antitumor activity [ 7 , 16 18 ], antioxidant activities [ 4 , 19 ], and so on. However, the bioactivity of other Catalpa plants was seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…Seven compounds (1, 4, 7-9, 12, and 13) were identified in the Smilacaceae family for the first time. The 16 known compounds were identified as trans-3,3 ,5,5 -tetrahydroxy-4methoxystilbene (1) [32], resveratrol (2) [33], 4-hydroxybenzoic acid (3) [34], 2-Ocaffeoylglycerol (4) [35], 1-O-caffeoylglycerol (5) [36], juncusyl ester B (6) [37], acertannin (7) [38], 2-O-(E)-feruloyl glyceride (8) [39], maplexin D (9) [40], trans-caffeic acid (10) [41], syringic acid (11) [42], 1-syringoyl-1,2-dihydroxyethane (12) [43], 3,5-dihydroxy-4-methoxybenzoic acid (13) [44], 1-(3,4,5-trimethoxyphenyl)-1,2,3-propanetriol ( 14) [45], 1-O-trans-ρ-coumaroylglycerol (15) [37], and trans-ρ-ethyl coumarate (19) [46] by comparing their spectroscopic data with reference values from the previously published literature.…”
Section: Chemical Identification Of Compounds 1-19mentioning
confidence: 99%